Histories, adaptations, and legacies of Tinker tailor soldier spy
1 online resource.
Keywords: "While providing critical reflections on the work across generations of enthusiasts, this is the first book exclusively dedicated to John le Carré's 1974 novel and its adaptations in radio, TV, and film. Tinker Tailor Soldier Spy stands among the most reproduced espionage tales of all time, with adaptations in television, radio, and film. Histories, Adaptations, and Legacies of Tinker Tailor Soldier Spy is a collection of essays by international experts who each provides an account of the story's currency across generations of audiences and scholars. Fans of the late John le Carré and the espionage genre will find here a comprehensive guidebook to the novel and its adaptations. Scholars, students, and amateur investigators alike will discover important historical, thematic, and theoretical ideas to explore and interrogate. Tinker Tailor Soldier Spy is a complex tale of the espionage trade and its crew of motley eccentrics. This collection decodes its puzzles, riddles, and enigmas regarding secrecy, betrayal, ethics, and survival in the context of the United Kingdom's place in the post-Second World War global order. A comprehensive guide for amateurs and an in-depth study of the novel's histories, legacies, and approaches for students and scholars"--